2022
DOI: 10.1093/plphys/kiac554
|View full text |Cite
|
Sign up to set email alerts
|

BELL1 interacts with CRABS CLAW and INNER NO OUTER to regulate ovule and seed development in pomegranate

Abstract: Pomegranate (Punica granatum) flowers are classified as bisexual flowers and functional male flowers. Functional male flowers have sterile pistils that show abnormal ovule development. In previous studies, we identified INNER NO OUTER (INO), CRABS CLAW (CRC) and BELL1 (BEL1), which were specifically expressed in bisexual and functional male flowers. However, the functions of ovule identity genes and the mechanism underlying ovule sterility in pomegranate remain unknown. Here, we found that the integument primo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Functional male flowers have sterile pistils that show abnormal ovule development. This result indicates that the vertical diameter of 8.1-13.0 mm is a critical stage for pomegranate ovule development [16]. In our study, pomegranate miRNAs of 'Taishanhong' bisexual flowers and functional male flowers were sequenced at the critical stages of pomegranate ovule development.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Functional male flowers have sterile pistils that show abnormal ovule development. This result indicates that the vertical diameter of 8.1-13.0 mm is a critical stage for pomegranate ovule development [16]. In our study, pomegranate miRNAs of 'Taishanhong' bisexual flowers and functional male flowers were sequenced at the critical stages of pomegranate ovule development.…”
Section: Introductionmentioning
confidence: 61%
“…According to Zhao's study [16], pomegranate ovule development was divided into three stages (initial ovule development stage: 5.0-10.0 mm; critical ovule abortion stage: 10.1-13.0 mm; ovule maturity stage: 13.1-18.0 mm). The pistils of bisexual and functional male flowers with vertical bud diameters of 5.0-10.0 mm (I), 10.1-13.0 mm (II), and 13.1-18.0 mm (III) were used as the test materials for miRNAs sequencing.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oil obtained from pomegranate seeds is known for its functional and beneficial health properties 5 . Apart from its commercial importance, pomegranate has become an attractive system for studying several valuable biological features, such as color formation in the fruit peel and aril 6 , phenotypic variations between soft-and hard-seeded varieties 7,8 , and the mechanism underlying ovule sterility [9][10][11] . Development of high-quality reference genome would be very useful for understanding the molecular mechanisms underlying these valuable biological features.…”
Section: Background and Summarymentioning
confidence: 99%
“…CRABS CLAW (CRC ) is an ancient member of the YABBY family in both gymnosperms and angiosperms (Zhao et al, 2023). Over two decades ago, Eshed et al (1999) found that sepal margins of Arabidopsis with 35S:AtCRC overexpression formed ectopic ovules and stigmas.…”
Section: Introductionmentioning
confidence: 99%